EDUCATIONAL AND SCHOOL MANAGERS TRAINING IN THE CONTEXT OF EDUCATIONAL REFORMS: CONSENSUS AND DISSENSUS - Oliveira Rescia, Ana Paula [UNESP]; Gentilini, Joao Augusto [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
This paper shows some of the results from a doctoral research on the educational and school managers training to the beginning of XXI century, in the context of decentralization and trends of educational reforms in Latin America at the end of 1980s and 1990s. Guided by a qualitative, bibliographic and documentary research, the methodological procedures had reference in studies conducted by international organizations, such as: UNESCO, ECLAC and ILPE as well as scholars from different management paradigms, considering the Latin-American education systems' needs. In Brazil, we sought to understand the requirements of transformation of local competences in planning and educational management after implications and managers training initiatives within this new reality. Therefore, it was analyzed for comparative purposes, three educational and school managers training programs in public schools: Management Circuit Program; Distance Learning Program for School Managers and the Managers' School Program of Public Basic Education. It was intended to identify the trends of each program for educational and school managers training, with a view to the changes occurred in our society and education and the requirements to acquire new skills and abilities. As conclusion, the research indicated that although the training programs have originated from different instances and explain various guidelines, everything converges to the same set of skills in educational and school managers training.
Keywords: Educational reform; Educational and school managers training; Skills and abilities